Assessment of service quality provided by Eastern College in Kota Kinabalu / Mohd Zamri Mohd Salleh - Mohd Salleh, Mohd Zamri (2015)
The objective of the study is to identify the assessment of service quality on the needs of physical resources and environment that relate to the dimension of service quality which is reliability, responsiveness, and empathy, besides that, the quality on the physical resources and environment, 4 P's elements and the good services offered by the PHEI contributes to the efficient performance of the institution thus determine the customer decision and satisfaction which will contributes to good reputation of the college and attract more customer to pursue their study at the college.